Agonist-Promoted Phosphorylation and Internalization of the Kappa Opioid Receptor in Mouse Brains: Lack of Connection With Conditioned Place Aversion - Chongguang Chen; Peng Huang; Kathryn Bland; Mengchu Li; Yan Zhang; Lee-Yu (Frontiers Media S.A., 2022)
Selective kappa opioid receptor (KOR) agonists are promising antipruritic agents and analgesics. However, clinical development of KOR agonists has been limited by side effects, including psychotomimetic effects, dysphoria, and sedation, except for nalfurafine, and recently. CR845 (difelikefalin). Activation of KOR elicits G protein- and β-arrestin-mediated signaling. KOR-induced analgesic and antipruritic effects are mediated by G protein signaling. However, different results have been reported as to whether conditioned place aversion (CPA) induced by KOR agonists is mediated by β-arrestin signaling. In this study, we examined in male mice if there was a connection between agonist-promoted CPA and KOR phosphorylation and internalization, proxies for β-arrestin recruitment in vivo using four KOR agonists. Herein, we demonstrated that at doses producing maximal effective analgesic and antiscratch effects, U50,488H, MOM-SalB, and 42B, but not nalfurafine, promoted KOR phosphorylation at T363 and S369 in mouse brains, as detected by immunoblotting with phospho-KOR-specific antibodies. In addition, at doses producing maximal effective analgesic and antiscratch effects, U50,488H, MOM-SalB, and 42B, but not nalfurafine, caused KOR internalization in the ventral tegmental area of a mutant mouse line expressing a fusion protein of KOR conjugated at the C-terminus with tdTomato (KtdT). We have reported previously that the KOR agonists U50,488H and methoxymethyl salvinorin B (MOM-SalB) cause CPA, whereas nalfurafine and 42B do not, at doses effective for analgesic and antiscratch effects. Taken together, these data reveal a lack of connection between agonist-promoted KOR-mediated CPA with agonist-induced KOR phosphorylation and internalization in male mice.